Antibacterial and antifungal activity of essential oils against some pathogenic bacteria and yeasts shed from poultry. (10th March 2016) - Ebani, Valentina Virginia; Nardoni, Simona; Bertelloni, Fabrizio; Giovanelli, Silvia; Rocchigiani, Guido; Pistelli, Luisa; Mancianti, Francesca
Abstract: Antibiotics have been used for decades in poultry diets to increase performance and decrease morbidity and mortality. The growing concern over the spreading of antibiotic‐resistant bacteria among animals and humans has resulted in the ban of the feed use of antibiotic growth promoters in livestock and in some cases additives derived from plants are used as alternative. Four commercial essential oils, from litsea ( Litsea cubeba (Lour.) Pers.), oregano ( Origanum vulgare L. subsp. hirtum ), marjoram ( Origanum majorana L.), thymus ( Thymus vulgaris L.) and their mixtures, were tested against pathogenic bacteria and yeasts that may be shed in faeces by poultry. In particular, the analysis were carried out against reference and wild bacterial strains of Salmonella enterica serovar Typhimurium, Yersinia enterocolitica, Listeria monocytogenes, Enterococcus durans, E . faecalis, and E . faecium, and wild isolates of Candida albicans, C . tropicalis, C . guilliermondii, C . krusei, C . parapsilosis and Saccharomyces cerevisiae . Essential oils had varying degrees of growth inhibition in relationship to the tested bacterial and yeast strains; however the best results were achieved by O . vulgare and T . vulgaris . All mixtures gave good results with reference and field bacterial strains, with MIC values ranging from 1.13 to 0.14 mg/ml. The mixture composed by O . vulgare, T . vulgaris and O . majorana appeared the most effective against the tested yeast isolates, with MIC 1.85 mg/ml. O . vulgare and T . vulgaris showed good antimicrobial activities, thus they seem useful not only to promote poultry growth, but also to control fastidious microorganisms commonly occurring in digestive tract of these animals. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Four commercial essential oils, from litsea ( Litsea cubeba (Lour.) Pers.), oregano ( Origanum vulgare L. subsp. hirtum ), marjoram ( Origanum majorana L.), thymus ( Thymus vulgaris L.) and their mixtures, were tested against pathogenic bacteria and yeasts that may be shed in feces by poultry. O. vulgare and T. vulgaris showed good antimicrobial activities, thus they seem useful not only to promote poultry growth, but also to control fastidious microorganisms commonly occurring in digestive tract of these animals.